Cirrhotic cardiomyopathy: is there any correlation between the stage of cardiac impairment and the severity of liver disease?. Issue 1 (1st January 2017) - Hammami, Rania; Boudabbous, Mouna; Jdidi, Jihen; Trabelsi, Fatma; Mroua, Fakher; Kallel, Rahma; Amouri, Ali; Abid, Dorra; Tahri, Nabil; Abid, Leila; Kammoun, Samir
ABSTRACT: Cirrhotic cardiomyopathy is associated with poor prognosis and risk of acute heart failure after liver transplantation or interventional procedures. We aimed to assess the relationship between the severity of cardiac impairment and hepatic disease. Eighty patients and eighty controls underwent echocardiography, tissue Doppler imaging and speckle tracking measures. We assess the correlation between echocardiographic parameters and Child and MELD scores. Systolic parameters function (s wave, p < 0.001) and global longitudinal strain ( p < 0.001) as well as diastolic parameters were significantly more impaired in cirrhotic patients compared to controls. There were no differences among the different groups in 'Child score' regarding systolic function as well as diastolic function. Paradoxically, the left atrium size correlated positively to both Child (p = 0.01, r = 0.26) and MELD scores (p = 0.02, r = 0.24). Left ventricular ejection fraction was significantly lower in decompensated patients as compared to compensated patients(p = 0.02).. We did not identify any association between severity of liver disease and cardiac dysfunction. Therefore, a transthoracic echocardiography should be performed in all cirrhotic patients before interventional and surgical procedures regardless of the severity of liver disease.